The Influence of Community and Societal Factors on the Occurrence of Wasting in Children Aged 3-5 Years - Hadi, Yuni Riska; Ristya Widi Endah Yani; Anisah Ardiana (Universitas Airlangga, 2024)
Background: Nutritional problems in toddlers remain a serious issue in several regions in Indonesia, including the working area of Songgon Health Center in Banyuwangi Regency. Aims: This study aims to analyze the influence of community and societal factors on wasting in children aged 3-5 years. Methods: The study uses a case-control approach with the entire population of toddlers in the working area of Songgon Primary Health Center as the target population. A cluster random sampling technique was used to obtain a sample of 166 individuals (83 wasting cases and 83 controls). Data were collected using a questionnaire that had passed validity and reliability testing. The collected data were analyzed through bivariate analysis using the chi-square test, and multivariate analysis using logistic regression. Results: The research results on wasting showed the following pvalues: t for family income 0.520 > α (0.05); occupation 0.263 > α (0.05 access to healthcare 0.121 > α (0.05); f immunization status 0.064 > α (0.05); education 0.436 > α (0.05); maternal knowledge 0.148 > α (0.05); family support 0.931 > α (0.05), and food security 0.430 > α (0.05), thus it can be interpreted these do not have a significant influence on wasting incidence. However, environmental sanitation significantly influences wasting incidence, as the p-value is 0.002 < α (0.05). Conclusion: The most influential factor in wasting incidence is environmental sanitation. Meanwhile, factors that have no influence are family income, mother’s occupation, healthcare access, immunization, education, knowledge, family support, and food safety.